Effect of Environmental Temperature on the Content of Impurity Li3V2(PO4)3/C in LiVPO4F/C Cathode for Lithium-ion Batteries - Zeng, Taotao; Fan, Changling; Wen, Zheng; Li, Qiyuan; Zhou, Zeyan; Han, Shaochang; Liu, Jinshui (Frontiers in Chemistry, 2018)
Abstract: Some previous studies show that the impurity Li3V2(PO4)3 in LiVPO4F will sacrifice its electrochemical performance. In this paper, we prove that the crystalline composition of LiVPO4F/C is mainly influenced by the environmental temperature. The content of Li3V2(PO4)3 formed in LiVPO4F/C is 0, 11.84 % and 18.75 % at environmental temperature of 10, 20, 30 ◦C, respectively. For the sample LVPF-30C, SEM pattern shows a kind of alveolate microstructure and results of selected area electron diffraction (SAED) is composed of two sets of patterns. LiVPO4F/C cathode without impurity phase Li3V2(PO4)3 was prepared at 10 ◦C. SAED results proves that the lattice pattern of it is the regular parallelogram. Electrochemical tests shows that only one flat plateau around 4.2 V appears in the charge/discharge curve, and the reversible capacity is 140.4 mAh·g-1 at 0.1 C, and 116.3 mAh·g-1 at 5 C. From these analyses, it is reasonable to speculate that synthesizing LiVPO4F/C at a low environmental temperature is a practical strategy to obtain the pure crystallite phase and good electrochemical performance.